Multimodal treatment efficacy differs in dependence of core symptom profiles in adult Attention-Deficit/Hyperactivity Disorder: An analysis of the randomized controlled COMPAS trial. (July 2022) - Selaskowski, Benjamin; Staerk, Christian; Braun, Niclas; Matthies, Swantje; Graf, Erika; Colla, Michael; Jacob, Christian; Sobanski, Esther; Alm, Barbara; Roesler, Michael; Retz, Wolfgang; Retz-Junginger, Petra; et al.
Abstract: There is broad consensus that to improve the treatment of adult Attention-Deficit/Hyperactivity Disorder (ADHD), the various therapy options need to be tailored more precisely to the individual patient's needs and specific symptoms. This post-hoc analysis evaluates the multimodal effects of first-line medication (methylphenidate [MPH] vs placebo [PLB]) and psychotherapeutic (group psychotherapy [GPT] vs clinical management [CM]) treatments on the ADHD core symptoms inattention, hyperactivity and impulsivity. For the two-by-two factorial, observer-blinded, multicenter, randomized controlled Comparison of Methylphenidate and Psychotherapy in Adult ADHD Study (COMPAS; ISRCTN54096201), 419 outpatients with ADHD were considered for analysis. ADHD symptoms were assessed by blind observer-rated and patient-rated Conners Adult ADHD Rating Scales before treatment (T1), 13 weeks (T2) and 26 weeks (T3) after T1, at treatment completion after 52 weeks (T4), and at follow-up (130 weeks, T5). MPH was superior to PLB in improving symptoms of inattention at almost all endpoints (observer-rated T2, T3, T4, T5; patient-rated T2, T3, T4), while a significant decrease in hyperactivity and impulsivity was at first found after 6 months of treatment. CM compared to GPT decreased inattention and impulsivity in the early treatment phase only (observer-rated T2, patient-rated T2, T3). In conclusion, while MPH seems to have a direct and sustained effect on inattention, premature medication discontinuation should particularly be avoided in patients with hyperactive-impulsive symptoms. Also, especially in high inattention and/or impulsivity presentations, initial individual patient management might be beneficial. Consequently, considering individual core symptom profiles may enhance the efficacy of treatments in adult ADHD. Highlights: Methylphenidate persistently improved adult ADHD symptoms of inattention. Reduction in hyperactivity and impulsivity after 6 months of methylphenidate intake. Promoting treatment adherence important in hyperactivity/impulsivity presentations.